2021
DOI: 10.1177/03915603211001677
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open partial nephrectomy for the management of highly complex renal tumors with PADUA score ⩾10: A single center analysis.

Abstract: Introduction: The aim of this study was to compare laparoscopic and open partial nephrectomy (PN) for renal tumors of high surgical complexity (PADUA score ⩾10). Methods: We retrospectively evaluated 93 consecutive patients who underwent PN at our department from January 2015 to September 2019. 21 patients underwent open partial nephrectomy (OPN) (Group A) and 72 underwent laparoscopic partial nephrectomy (LPN) (Group B). All OPNs were performed with a retroperitoneal approach, while all LPNs were performed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…20,38 One study noted a lower rate of overall postoperative complications in LPN compared to OPN (15.3% vs 57.1%). 33 Three studies demonstrated lower rates of overall complications 21,34,35 in RPN, and similar findings were noted in a review by Bravi et al 24 when evaluating the major complications against the three surgical approaches. High-grade complications are commonly seen in OPN.…”
Section: Evidence Synthesissupporting
confidence: 58%
See 1 more Smart Citation
“…20,38 One study noted a lower rate of overall postoperative complications in LPN compared to OPN (15.3% vs 57.1%). 33 Three studies demonstrated lower rates of overall complications 21,34,35 in RPN, and similar findings were noted in a review by Bravi et al 24 when evaluating the major complications against the three surgical approaches. High-grade complications are commonly seen in OPN.…”
Section: Evidence Synthesissupporting
confidence: 58%
“…Bravi et al 24 noted a statistical significance in the CR between LPN and RPN, accounting for seven and one case respectively ( p = 0.002). Chiancone et al 33 noted a total of 4 out of 72 LPN cases which required conversion to open approach. Similar results were demonstrated in Pazeto et al 25 with reported three LPN cases requiring conversion to OPN, although this was statistically not significant ( p = 0.07).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The meta-analysis encompassed six studies that provided data on operative time. Additionally, the results demonstrated that there was no statistically significant distinction in operative time between the groups that underwent LPN and OPN (WMD 3.84 mins, 95% CI -3.57 to 11.26; p = 0.31) ( 15 18 , 20 , 21 ). After pooling data from seven separate studies, the LPN cohort demonstrated a shorter duration of hospitalization in comparison to their OPN counterparts (WMD -2.06 days, 95% CI -2.62 to -1.50; p < 0.00001) ( Figure 2 ) ( 15 21 ).…”
Section: Resultsmentioning
confidence: 90%
“…The collective findings indicated that LPN was linked to lower blood loss compared to OPN (WMD: -34.05 mL, 95% CI: -55.61 to -12.48; p = 0.002). Nevertheless, no significant distinction was observed in the transfusion rate prevalence between LPN and OPN (OR 0.33, 95% CI 0.11, 0.98; p = 0.05) (three studies; Figure 3 ) ( 15 , 20 , 21 ). The analysis revealed that a discernible disparity in the prevalence of warm ischemia time between LPN and OPN was not evident (WMD 4.03 mins, 95% CI -1.72 to 9.78; p = 0.17) (based on findings from six studies; Figure 4 ) ( 15 19 , 21 ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation